2021
DOI: 10.1371/journal.pone.0255901
|View full text |Cite
|
Sign up to set email alerts
|

Cancer caregivers unmet needs and emotional states across cancer treatment phases

Abstract: Study objective To investigate the association between family cancer caregivers’ unmet daily needs and emotional states of depression, anxiety and stress across their care recipient’s treatment phases. Method A cross-sectional study design and self-report questionnaires were used. Family caregivers (N = 237) of cancer patients in ambulatory cancer clinics were recruited from May to December 2017, and completed a sociodemographic and medical questionnaire, the Depression Anxiety Stress Scale and Needs Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(67 reference statements)
2
15
0
Order By: Relevance
“…The prevalence of depression has been shown to be higher among family caregivers when cancer patients are in receipt of treatment [ 13 ]. Yang et al focused on the unmet needs and emotional states of caregivers in the inpatient setting and found that the unmet needs of caregivers had a major effect on the depression of caregivers when the patient was undergoing treatment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of depression has been shown to be higher among family caregivers when cancer patients are in receipt of treatment [ 13 ]. Yang et al focused on the unmet needs and emotional states of caregivers in the inpatient setting and found that the unmet needs of caregivers had a major effect on the depression of caregivers when the patient was undergoing treatment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although an association between the unmet needs of family caregivers and the QoL of patients may be found, the factors accounting for this association are poorly understood. Sklenarova and colleagues demonstrated that many caregivers suffer anxiety and depression when patients are undergoing treatment [ 13 ]; Yang et al found that unmet needs play a major role in generating negative psychological feelings among family caregivers [ 14 ]; and Heckel identified a positive correlation between the unmet needs of caregivers and their likelihood to suffer depression [ 15 ]. Depression among caregivers is also likely to be associated with the QoL of childhood cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our qualitative findings underscore a lack of information as a salient concern among ECD/HN caregivers. When left unmet, informational needs have the potential to contribute to psychological and physical health consequences over time 33 and thus crucial to recognize and address.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our qualitative findings underscore a lack of information as a salient concern among ECD/HN caregivers. When left unmet, informational needs have the potential to contribute to psychological and physical health consequences over time 33 and thus crucial to recognize and address. The capacity of ECD and HN caregivers to derive positive value from caregiving (benefit finding) and connect with a sense of meaning and purpose (meaningmaking), despite unmet needs, supports the burgeoning literature documenting caregiver resilience and growth, 14,34 and importantly, extends it to rare cancer caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In oncology wards, where patients spend the last days of their life and experience significant amount of pain and suffering,[ 1 2 ] oncology nurses, as key members of healthcare teams who spend significant amount of time with cancer patients during all stages of their disease,[ 2 ] are the primary caregivers and active companions of these patients and may face many challenges in the process of care delivery. [ 3 ] Oncology nurses are exposed to many emotional problems, such as discomfort, helplessness, guilt, and difficulty managing and coping with negative emotions during care. [ 1 2 ] Providing support to cancer patients and their families requires significant mental and emotional involvement on the part of the caregivers.…”
Section: Introductionmentioning
confidence: 99%